2015
DOI: 10.1088/0004-637x/812/1/27
|View full text |Cite|
|
Sign up to set email alerts
|

Alma Observations of the Transition From Infall Motion to Keplerian Rotation Around the Late-Phase Protostar TMC-1a

Abstract: We have observed the Class I protostar TMC-1A with Atacama Millimeter/submillimeter Array (ALMA) in the emissions of 12 CO and C 18 O (J = 2−1), and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
183
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(217 citation statements)
references
References 63 publications
33
183
1
Order By: Relevance
“…IRAS 04365+2535 is one of the few in our sample with a detected Keplerian rotating disk (e.g., Harsono et al 2014;Aso et al 2015). Our best-fit model for it has a disk with a radius of R 140 au disk and a mass of…”
Section: Iras 04365+2535mentioning
confidence: 94%
See 3 more Smart Citations
“…IRAS 04365+2535 is one of the few in our sample with a detected Keplerian rotating disk (e.g., Harsono et al 2014;Aso et al 2015). Our best-fit model for it has a disk with a radius of R 140 au disk and a mass of…”
Section: Iras 04365+2535mentioning
confidence: 94%
“…Harsono et al (2014) observed Keplerian rotation in the IRAS 04365+2535 disk with 13 CO observations and modeled the disk with a radius of 80-100 au and inclination of 55°. Similarly, Aso et al (2015) modeled infall and rotation detected toward the protostar in C 18 O emission and found that the disk has an inclination of 65°and a radius of 100 au. These results are both consistent with our own model fits.…”
Section: Iras 04365+2535mentioning
confidence: 99%
See 2 more Smart Citations
“…Yen et al 2013). The rotation velocity distribution of TMC-1A is given by Aso et al (2015). The radius of the Keplerian disk is about 100 AU and the central star mass is estimated as 0.68M⊙.…”
Section: Tmc-1a (L1534)mentioning
confidence: 99%